A new algorithm for estimating radioxenon concentrations. (March 2023) - Eslinger, Paul W.; Schrom, Brian T.; Warren, Glen A.
Abstract: A new algorithm (Xcounts) is introduced for estimating the activity concentrations of the xenon isotopes 131m Xe, 133m Xe, 133 Xe, and 135 Xe using beta-gamma coincidence data. The algorithm simultaneously estimates the decay counts associated with the four xenon isotopes, background, and radon in contrast to the net-counts method that uses sequential residual removal to account for background and interferences. Calibration data for background counts are determined from gas-background measurements and simulation. In Xcounts, the false positive count rates for 131m Xe and 133m Xe are lower than those for 133 Xe and 135 Xe. This algorithm appears to reliably detect the metastable isotopes at lower activity levels than the net-counts method and have similar performance for the other isotopes. Highlights: New approach for estimating radioxenon activity concentrations in air. Approach uses simultaneous isotope count estimation using beta-gamma coincidence data. Background and radon daughter counts are estimated rather than subtracted. Performance compares well with existing models for 133 Xe and 135 Xe. Detection limits for 131m Xe and 133m Xe are lower than for net-count based algorithms.